(untitled) (Journal of the College of Basic Education, 2022)
The paper presents a proposed method with algorithms written in Matlab language for solving a system of linear functional-differential equations numerically using fifth-order-six-stage Nyström ’s method. This method has been developed to find the numerical evolutions for three types (retarded, neutral and mixed) of n th order linear functional differential equations. Comparison between the numerical and exact results has been given for three numerical examples for solving three types of linear functional differential equations. Finally, the results are arranged in tabulated form and suitable graphing is given for the examples.